Cost-effectiveness of percutaneous mitral repair for patients with severe secondary mitral regurgitation: an updated evaluation using a modelling approach based on COAPT final data after 5-year follow-up - Xavier Armoiry; Peter Auguste; Martin Connock; Jean-Francois Obadia (BMJ Open)
Objectives To evaluate the cost-effectiveness of percutaneous repair (PR) for secondary mitral regurgitation.Design An economic evaluation using a time-varying Markov model comprising three states to assess the cost and effectiveness of PR added to guideline-directed medical treatment (GDMT) compared with GDMT alone. Clinical outcomes considered within the model were overall survival and heart failure (HF) hospitalisations (HFH), and the incremental cost-effectiveness ratio (ICER) was calculated. Cost data were derived from a literature search. Sensitivity analyses were undertaken.Setting The French healthcare system perspective assuming a lifetime horizon.Participants Published data at 5 years obtained from patients enrolled in the Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy for Heart Failure Patients with Functional Mitral Regurgitation study.Results In our base case, we chose cubic spline models to extrapolate overall survival, and we used log-logistic models to estimate cumulative HFH. After discounting, the model generated life-years of 3.843 years and 3.055 years for PR+GDMT and GDMT, respectively. Discounted total quality-adjusted life-year (QALY) values were 2.572 and 1.945 for PR+GDMT and GDMT, respectively (incremental 0.627 QALY). Discounted total costs were €42 709 and €20 732 for the intervention and the control groups, respectively (incremental €21,977), resulting in an ICER of €35,068/QALY. At a threshold of €50 000 per QALY, PR had a 0.85 probability of being cost-effective.Conclusion Updated trial data have enabled investigators to provide a more reliable estimation of the ICER, which suggests that PR has good value for money compared with GDMT alone.